Lean TMM application of lean test maturity model framework in an agile environment - Ibañez, Jettrey A. (University of the Philippines Diliman, 2011)
The Software Delivery (SD) Test Team has been established to provide quality control of web applications developed by the Software Delivery Team to other business groups within Company X. Since the creation of the team, there haven't been standardized processes that were being followed in terms of testing. Normal procedures include reviewing of requirements, creating test cases, testing upon delivery of the software, and providing sign off. Aside from these activities, the roles and responsibilities for each level of testers had not been distinguished, and the current process lacks some supporting activities such as peer review, post mortem and project evaluation that could enhance the quality of testing; thus, increasing the chances of delivering high quality applications. This insufficiency in testing activities led to : delay in delivery of the applications, defects found in production, slow knowledge transfer rate, high failure cost, complaints from business users. Now that the team has grown significantly and is becoming more and more organized, the Lean Test Maturity Model (TMM) project is proposed to align the test processes with industry standards, and at the same time, with the goals of the organization. Lean TMM will map the current test processes with those of the Test Maturity Model Level 3 Framework while maintaining the "lean factor", where activities that are not beneficial or does not fall within the objectives of the organization are removed